Working memory capacity moderates the effect of hearing aid experience on phonological processing performance - Ning, Ruijing; Holmer, Emil; Danielsson, Henrik; Signoret, Carine; Micula, Andreea; Rönnberg, Jerker (Frontiers in Neuroscience, 2025)
PurposeIndividuals with acquired hearing impairment often experience declines in phonological processing abilities, a phenomenon thought to be mediated by working memory capacity (WMC). However, the role of hearing aid use in this context remains underexplored. Therefore, in the current study, we aimed (1) to tease apart the effect of hearing impairment and hearing aid use on phonological processing performance, and (2) to investigate the effect of hearing aid use on phonological processing in more detail, while considering the involvement of WMC.MethodUsing mixed effect models, we investigated rhyme judgment performance and its reliance on WMC among three groups of participants: a group of hearing aid users (n = 202), a group of hearing-impaired individuals without hearing aid (n = 54), and a group of normal hearing controls (n = 201). We also examined how years of hearing aid use was associated with rhyme judgment performance and its reliance on WMC in hearing aid users.ResultsWe found that hearing impairment was associated with increased dependence of rhyme judgment performance on WMC regardless of the use of hearing aids. Furthermore, hearing aid use was overall positively associated with rhyme judgment performance, with this relationship influenced by variations in WMC.ConclusionWMC influences the effectiveness of hearing aids for phonological processing. This role may result from working memory’s involvement in the processing of output signals from hearing aids, as well as in the strategies hearing aid users implement to deal with phonological processing tasks.